A facile one-pot strategy for the preparation of porous polymeric microspheres via UV irradiation-induced polymerization in emulsions. Issue 7 (31st January 2023) - Tao, Junjie; Wu, Kaiyun; Chen, Yaxin; Li, Wei; Gu, Yao; Liu, Ren; Luo, Jing
Abstract : In this study, a facile one-pot strategy was developed to prepare porous polymeric microspheres via photopolymerization, where organic solvents functioned as porogens. Abstract : In this study, a facile one-pot strategy was developed to prepare porous polymeric microspheres via photopolymerization, where organic solvents functioned as porogens. In this strategy, an oil phase containing organic solvents and photopolymerizable materials was stabilized in water to form a stable oil-in-water emulsion. Upon UV irradiation, the photopolymerizable materials (photosensitive monomers/photosensitive prepolymers) underwent polymerization to form microspheres and the subsequent removal of organic solvents left pores in microspheres, leading to the generation of porous polymeric microspheres with high yielding. The effects of organic solvents and the chemical structure and concentration of photopolymerizable materials on the microsphere structure were systematically explored. It was found that the polarity of the organic solvents played a decisive role in the preparation of porous microspheres. In addition, the increases in the solvent content and functionalities of photopolymerizable materials were more favorable for the generation of porous microspheres. This strategy could be applicable for a wide selection of photopolymerizable materials, which endowed this strategy with good applicability. The preparation of porous microspheres by this method was facile and easy to handle, enabling the scalable preparation of porous microspheres. In addition, the whole process can be completed within a few minutes at ambient temperature, which was time-saving and energy-saving.